2021
DOI: 10.21037/apm-21-1677
|View full text |Cite
|
Sign up to set email alerts
|

High-order aberration changes after femtosecond LASIK surgery in patients with high myopia

Abstract: Background: To investigate the relationship between high-order aberration (HOA) changes and RCST/CT (residual corneal stroma thickness/corneal thickness) after femtosecond LASIK surgery.Methods: A total of 65 eyes from 39 patients with high myopia, who had femtosecond (FS) laser-assisted in situ keratomileusis (LASIK) surgery performed in our hospital, were included in this study. HOA and central corneal thickness were measured preoperatively and at 1 week, 1 month, and 3 months after FS-LASIK by Sirius Schei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Adib-Moghaddam et al [ 12 ] followed up the clinical results 18 months after Trans-PRK and found that corneal spherical aberration and coma were significantly increased after the surgery. Feng et al [ 19 ] found that corneal coma, spherical aberration, and total HOAs were significantly increased at 1 week, 1 month, and 3 months after the surgery compared with the preoperative values. These results were consistent with our report.…”
Section: Discussionmentioning
confidence: 99%
“…Adib-Moghaddam et al [ 12 ] followed up the clinical results 18 months after Trans-PRK and found that corneal spherical aberration and coma were significantly increased after the surgery. Feng et al [ 19 ] found that corneal coma, spherical aberration, and total HOAs were significantly increased at 1 week, 1 month, and 3 months after the surgery compared with the preoperative values. These results were consistent with our report.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a statistically signi cant difference in RMS spherical aberration in both groups between the preoperative and postoperative periods. Changes in corneal asphericity caused by corneal epithelial healing and matrix brosis are primarily responsible for increased spherical aberration (31,32). Furthermore, corneal asphericity was signi cantly correlated with the preoperative MRSE (25,33).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding of the human ocular refractive system is constantly improving with the rapid development of physical optics. In particular, higher order aberration (HOA) has enhanced the study of visual quality [12][13][14] and has become an important index in research on refractive surgery. Spherical-like aberration or LSA is a higher order aberration with significant impact on visual quality.…”
Section: Discussionmentioning
confidence: 99%